Analisis Unjuk Kerja TCP Sack Menggunakan Antrian Random Early Detection - Rinny Asasunnaja; Bambang Sugiantoro (JISKA (Jurnal Informatika Sunan Kalijaga), 2022)
As time goes by, the current technology is also developing very rapidly, the rapid development of technology, especially on the internet network is also developing so that it is expected to continue to provide the best quality to meet the growing and fast information needs. An internet network is highly demanded of its best quality, one of which is in the spotlight to be developed, namely TCP Transmission Control Protocol. The efficiency and smoothness of the data transmission process is the most important thing in a communication network. TCP is one aspect that supports today’s fast internet, with TCP we can exchange information accurately, quickly, and well. In this study, researchers are interested in analyzing the performance of TCP Sack using the Random Early Detection queue. By doing this research is expected to know the performance of TCP Sack by looking at the parameter values of packet delivery ratio, throughput, end to end delay, and packet drop. Based on the results of the analysis, it can be concluded that end-to-end delay parameter testing on the TCP Sack still has poor performance, while for testing the packet delivery ratio, throughput, and packet drop TCP Sack already has good performance.